2020
DOI: 10.3390/pathogens9060460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunogenic Antigens of Naegleria fowleri Adjuvanted by Cholera Toxin

Abstract: The intranasal administration of Naegleria fowleri lysates plus cholera toxin (CT) increases protection against N. fowleri meningoencephalitis in mice, suggesting that humoral immune response mediated by antibodies is crucial to induce protection against the infection. In the present study, we applied a protein analysis to detect and identify immunogenic antigens from N. fowleri, which might be responsible for such protection. A Western blot assay of N. fowleri polypeptides was performed using the serum and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…21 Moreover, in a recently published work, we applied a protein analysis to detect and identify immunogenic antigens from N. fowleri, which might be responsible for such protection and we found that IgA and IgG isotypes of serum or nasal washes responded mainly to the polypeptidic bands of 250, 100, 70, 50, 37 and 19 kDa, especially in the third and fourth immunization. 14 This finding led us to the purification of the 250-kDa polypeptide band (Figure 1), which was used in all our immunization groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Moreover, in a recently published work, we applied a protein analysis to detect and identify immunogenic antigens from N. fowleri, which might be responsible for such protection and we found that IgA and IgG isotypes of serum or nasal washes responded mainly to the polypeptidic bands of 250, 100, 70, 50, 37 and 19 kDa, especially in the third and fourth immunization. 14 This finding led us to the purification of the 250-kDa polypeptide band (Figure 1), which was used in all our immunization groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in previous work, some as myosin II heavy chain fragment: actin fragment and cysteine protease fragment. 14 For example, it has been reported that cysteine protease has the ability to destroy host tissue, 22 suggesting that this protein could be involved in the destruction and pathogenesis of N. fowleri. [22][23][24] Although actin and myosin have been reported to participate in phagocytosis activity as both proteins are concentrated around phagocytic cups of N. fowleri, 25 antibodies to these two proteins are unlikely to play a direct role in protective immunity as they will not gain access to the cytoplasm in the living organism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations